Measurements and simulation of RF heating of implanted stereo‐electroencephalography electrodes during MR scans. Issue 4 (21st February 2018) - Bhusal, Bhumi; Bhattacharyya, Pallab; Baig, Tanvir; Jones, Stephen; Martens, Michael
Abstract : Purpose: To assess RF‐induced heating during MRI of patients with implanted stereo‐electroencephalography electrodes. Methods: Simulations and experimental measurements using phantom and a head‐only transmit/receive coil on a 3T MR system were performed to evaluate temperature increases at the tip of an 8‐contact stereo‐electroencephalography electrode and an insulated wire partially immersed into the phantom. The lengths of wire producing maximum (resonant condition) and minimum (anti‐resonant condition) heating were evaluated for different entry modes and penetration depths. Results: For both wire and stereo‐electroencephalography electrode, resonant lengths were close to odd integral multiples of RF quarter wavelength in air and antiresonant length close to even integral multiples of RF quarter wavelength, both being unaffected by the entry mode. In the resonant condition, temperature increased by as much as a factor of 10 higher than that at antiresonant condition. Larger penetration depths did not change resonant length, but did lead to increased RF heating. Conclusion: For the partially immersed implants like stereo‐electroencephalography electrode, the resonant lengths were found to be independent of the penetration depths and entry modes, although the temperature increases may vary. Avoiding such lengths of cables can reduce the risk of tissue heating during in vivo MRI.